Single haps airship interference to fixed wireless access station / Badliruzi Abdul Rahman - Abdul Rahman, Badliruzi (2011)
High Altitude Platform Station (HAPS) technology is a new technology that can perform the task currently handled terrestrial and satellite system. It is located at an altitude of 20 km to 25 km above the ground level to provide wireless access over a 400 km radius of footprint. The main objective of this paper is to study the interferences from the HAPS airship to the Fixed Wireless Access (FWA) station on the ground. Impact of using HAPS airship to the surrounding of FWA stations is analyzed. System performance is determined by the ratio of interfering powers to noise power, 1/N ratio. All equations and methodologies used in interference and interference to noise ratio evaluation is done base on International Telecommunication Union Recommendation (ITU-R). MATLAB software is used for simulation of the interference. The calculation is made for only the case of single entry and two under clear-sky condition. The minimum of interference to noise ratio, 1/N of the downlink system in clear-sky has been obtained in order to determine the minimum interference level of HAPS downlink system.